(untitled) (Archives of Mechanics - Test, 2008)
The thermomechanical response of beams made up of thermoplastic polymer is analysed in the case of cyclic bending. The material behavior is modelled by a viscoelastic law depending on temperature and frequency. Inertia effects are neglected. The stress, strain and temperature distributions are expressed as functions of the beam geometry, the loading parameters and the material characteristics. The stability of the steady-state solutions is analysed with use of a linear perturbation approach. The conditions for thermal runaway (thermo-mechanical instability) are explored.